Contrasting Effects of Natural Selection on Human and Chimpanzee CC Chemokine Receptor 5 - Wooding, Stephen; Stone, Anne C.; Dunn, Diane M.; Mummidi, Srinivas; Jorde, Lynn B.; Weiss, Robert K.; Ahuja, Sunil; Bamshad, Michael J. (American journal of human genetics, 2005)
Human immunodeficiency virus type 1 (HIV-1) evolved via cross-species transmission of simian immunodeficiency virus (SIVcpz) from chimpanzees ( Pan troglodytes). Chimpanzees, like humans, are susceptible to infection by HIV-1. However, unlike humans, infected chimpanzees seldom develop immunodeficiency when infected with SIVcpz or HIV-1. SIVcpz and most strains of HIV-1 require the cell-surface receptor CC chemokine receptor 5 (CCR5) to infect specific leukocyte subsets, and, subsequent to infection, the level of CCR5 expression influences the amount of HIV-1 entry and the rate of HIV-1 replication. Evidence that variants in the 5′ cis-regulatory region of CCR5 ( 5′CCR5) affect disease progression in humans suggests that variation in CCR5 might also influence the response of chimpanzees to HIV-1/SIVcpz. To determine whether patterns of genetic variation at 5′CCR5 in chimpanzees are similar to those in humans, we analyzed patterns of DNA sequence variation in 37 wild-born chimpanzees (26 P. t. verus, 9 P. t. troglodytes, and 2 P. t. schweinfurthii), along with previously published 5′CCR5 data from 112 humans and 50 noncoding regions in the human and chimpanzee genomes. These analyses revealed that patterns of variation in 5′CCR5 differ dramatically between chimpanzees and humans. In chimpanzees, 5′CCR5 was less diverse than 80% of noncoding regions and was characterized by an excess of rare variants. In humans, 5′CCR5 was more diverse than 90% of noncoding regions and had an excess of common variants. Under a wide range of demographic histories, these patterns suggest that, whereas human 5′CCR5 has been subject to balancing selection, chimpanzee 5′CCR5 has been influenced by a selective sweep. This result suggests that chimpanzee 5′CCR5 might harbor or be linked to functional variants that influence chimpanzee resistance to disease caused by SIVcpz/HIV-1.